PERSEPSI MASYARAKAT JAWA TERHADAP LARANGAN MENIKAH DI BULAN MUHARRAM DITINJAU DARI HUKUM ISLAM (AL MUNAZHZHARAH, 2019)
This study focused on the community's views on the prohibition of marriage in the month of Muharram, which was born since ancient times, especially among the community of Bandar Kelurahan Mojoroto, Kediri City. The author uses the type of field research (Field Research), using a descriptive qualitative approach with data techniques through observation, interviews, and field notes. From the results of the analysis that the researchers have done, the community in bandar lor village mojoroto sub-district of Kediri did not dare to have a wedding in the month of Muharram because the month of Muharram was a sacred month that was sanctified by some Javanese communities that were devoted to purifying themselves, many did tiralaks aimed at draw closer to Allah. Judging from Islamic law, the prohibition of marriage in Muharram is not true. Because in the view of Islamic law, the month of Muharram is included in the fourth month which is glorified by Alla SWT.